Renormalized electric and magnetic charges for O(r n ) large gauge symmetries - Javier Peraza (Journal of High Energy Physics, 2024)
Abstract In this work we present the construction of a renormalized symplectic form on an extended phases space where the higher order large gauge transformations (LGT) act canonically. The expressions of the sub n -leading electric charges associated with each O(r n ) LGT are then obtained, in agreement with the expressions previously proposed in [1] by means of the tree-level sub n -leading formulas. We also present the duality extension of the extended phase space, computing the full electromagnetic charge algebra, showing a tower of central extensions.